Design of E-Grant Application Data Warehouse - A.A Ngurah Narendra; Santi Ika Murpratiwi; Made Sudarma (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
Grants is a program launched by the government as a means to develop the potential of the region or contribute to society in the form of money or objects In submitting as Grant there are many sources of data stored in the system e -Grant, The amount of the proposal Grant is very much in each period so as to be reorganized, One solution for the storage of e-submission of the Grant is to build a data warehouse, Due to the technological development of data warehouse will be able to support the creation of a single access door managerial parties in obtaining information in the data warehouse, The design of the data warehouse were calculated using a four step Kimball, Methods Kimball 4 step has the advantages of a more compact, dynamic, and supports the creation of a data warehouse that is structured output of the data warehouse to the e-Grant in the form of Reports Grant and a recapitulation of Grant where reports Grant is being used as an attachment to a defense in response to the report Expenditure Provincial Bali whereas Summary of Grants used for List SKPD to evaluate the Grant recipient.